PREPARATION OF DRY SPECIMEN OF BONES - Siddiqui, Muhammad Aaqil (Journal of Ayub Medical College Abbottabad, 1990)
ABSTRACT: Dry bone specimen preparation only by fixing with 10% Formalin, boiling with water and hard brushing removes important marks and allows the growth of Fungi and other microorganisms over them. Therefore, to prepare a presentable dry bone specimen for the museum and students, a new method consisting of three steps, a) removal of soft tissue by softening, b) extraction of fat by chloroform and c) bleaching with hydrogen peroxide is described. The method produces satisfactory specimen and can be used to prepare the articulated skeleton for museum, instead of importing a plastic model from abroad